Semiotic Dimension Deconstruction in the First Movement of "Spring" by Vivaldi (Jurnal Seni Musik, 2023)
Music is a means of expressing feelings and aesthetics in the human mind and heart. Through increasing human creativity, this media for expression comes in many types, one of which is program music, whose compositional construction is based on the composer's imagination to describe a character, atmosphere, or an event. Allegro of “Concerto No. 1 in E major, Op. 8, RV 269: Spring (La primavera)”, as the first movement of the program music The Four Seasons from Vivaldi, is famous for depicting the atmosphere of spring filled with birdsong, the wind blowing, to the sound of the river flowing. Therefore, this study intents to thoroughly examine those representations of this atmosphere through the deconstruction of the semiotic dimension. As an inductive qualitative research, Peirce's semiotic theory and the descriptive analysis data method are applied. Based on Peirce's semiotic theory, the description of the spring atmosphere is present in interpretant through the imitation of bird sounds, river flow, and storms; harmonic progressions, melodic motifs, musical technique ornaments, and collective structures in objects; as well as sonnets in representamen. Thus, it can be summarized that the illustration of the atmosphere in the title and sonnet is closely related to the music notation, meaning they are inseparable. In the past few years, an akin exploration that focuses on Vivaldi's works through the semiotic perspective was absent; hence, this study plays a huge part in its research contribution to the field of knowledge.